Issues on livestock technology Development on smallholder farms in Ethiopia - Asamenew, G. (Christian Relief and Development Association, 1992)
Discusses some methodological issues on livestock technology Development in Ethiopia, also stresses that livestock projects that appeared promising were abandoned after project funding ceased because of mainly the inappropriateness of many of the methods used in the design and execution of the projects. Argues that livestock technology Development and transfer have to follow a bottom-approach instead of top-down approach, and outlines farm-level contributions of livestock; indicates that livestock have output, input, asset and security, and investment functions on smal mixed farms.